Perspectives of ESL Learners on the Integration of Technology in English Language Learning Process: An Evidence-Based Research - Lamo, Padma; Dhuli, Raju; Larsari, Vahid Norouzi (EDUPEDIA Publisher, 2023)
Technology is a part and parcel of this information age; no sphere of learning is untouched by it. The field of ELT/EFL/ESL is no exception. The current paper is an attempt to understand how the use of technology has been received in the field of English as a second language and gather perspectives from the learners of the English language about the effect of technology in their learning. The paper explores various modes of e-learning and how the tools aid traditional ways of teaching and learning English as a second language. An attempt has been made to trace new trends in learning with the ever-evolving technology in the 21st century. This paper has reviewed a few significant researches to give a perspective on the efficacy of modern technologies in learning English for ESL students.